A theoretical model and verification of soil column deformation under impact load based on the Duncan-Chang model - Jianqiu, Huang; Zhuo, Jin; Haiping, Wang; Tao, Ling; Xuejun, Peng; Yu, Tang; Qin, Liu; Xi, Li (Frontiers in Materials, 2024)
The dynamic compaction method has been widely adopted in foundation treatment to densify the soil fillers. However, for the complexity of the impact behavior and soil mechanical properties, the theoretical research of dynamic compaction lags behind its practice for complex soil properties and stress paths. This paper presents a theoretical model applied to describe soil column plastic deformation under impact load. The relationship among stress increment, strain increment, and plastic wave velocity was derived from the aspect of propagation characteristics of stress waves in soil first. Combined with the Duncan-Chang Model, a one-dimensional theoretical model was established then. A numerical model was developed further to check the performance of the model. It showed that the deformation at the end of the soil column was mushroom-shaped. Both the axial and lateral deformation increased with the impact velocity. While some particles located at the side of the soil column end may splash under repeated impact. The theoretical deformations of the soil column were consistent with the experimental results both in the direction of axial and lateral.